Parental care and altitudinal range extension of the endemic frog Bryophryne gymnotis (Anura: Craugastoridae) in the Andes of southeastern Peru - Mamani, L (2017)
Amphibians have developed different strategies to protect eggs, tadpoles, and froglets. Seven modes of parental care are known: egg attendance, egg transport, tadpole attendance, tadpole transport, tadpole feeding, internal gestation, and froglet transport. Brachycephaloidea (Terrarana) includes 1073 species f which are known to provide parental care. In Peru, seven species of Craugastoridae are known to exhibit parental care, including Bryophryne cophites, Lynchius oblitus Motta, Chaparro, Pombal, Guayasamin, De la Riva, and Padial, 2016.